Peningkatan Keterampilan Menulis Teks Eksposisi Menggunakan Model Cooperative Integrated Reading and Composition (CIRC) di Kelas V Sd Negeri 07 Pasaman Kabupaten Pasaman Barat - Mardiah, Ainul; Muhammadi, Muhammadi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to improve exposition text writing skills using the Cooperative Integrated Reading and Composition (CIRC) model in class V of SD Negeri 07 Pasaman, West Pasaman Regency. The CIRC model is applied to encourage students to improve their exposition text writing skills. This research was conducted in 2 cycles with the stages of planning, implementation, observation, and reflection. The research subjects were fifth-grade students of SD Negeri 07 Pasaman, with data collected through test and non-test techniques, while the research instruments were test and non-test sheets. Data analysis was carried out using the percentage formula. The results showed that the use of the CIRC model can significantly improve the skill of writing an exposition text. In cycle I, the average score on the Teaching Module aspect was 90 with qualifications (A), increasing in cycle II, which obtained an average of 95 with qualifications (A), the results of observations of the teacher's aspects and aspects of students in cycle I meeting I received the same score of 83.33 with good qualifications (B) and increased in cycle I meeting II to 87.5 in the aspects of teachers and students. The average for teacher and learner activity scores in cycles I and II is 85.41 with qualifications (B). In cycle II, the score for teacher activity was 95.83, and learner activity was 95.83 with qualification (A)